The universal scaling characteristics of tropical oceanic rain clusters. Issue 11 (5th June 2017) - Teo, C.‐K.; Huynh, H.‐N.; Koh, T.‐Y.; Cheung, K. K. W.; Legras, B.; Chew, L. Y.; Norford, L.
Abstract: Using multiyear satellite rainfall estimates, the distributions of the area, and the total rain rate of rain clusters over the equatorial Indian, Pacific, and Atlantic Oceans was found to exhibit a power law f S s s − ζ S, in which S represents either the cluster area or the cluster total rain rate and f S ( s ) denotes the probability density function of finding an event of size s . The scaling exponents ζ S were estimated to be 1.66 ± 0.06 and 1.48 ± 0.13 for the cluster area and cluster total rain rate, respectively. The two exponents were further found to be related via the expected total rain rate given a cluster area. These results suggest that convection over the tropical oceans is organized into rain clusters with universal scaling properties. They are also related through a simple scaling relation consistent with classical self‐organized critical phenomena. The results from this study suggest that mesoscale rain clusters tend to grow by increasing in size and intensity, while larger clusters tend to grow by self‐organizing without intensification. Key Points: The size and rainfall distributions of observed tropical rain clusters appear to be universal across the oceans Scaling exponents of cluster rain rate and cluster area are related in a way that is consistent with self‐organized critical phenomena Cluster areal rain efficiency at the mesoscale increases with cluster area but is practically constant at larger scales